Nutritive Evaluation of the Bambara Groundnut Ci12 Landrace [Vigna subterranea (L.) Verdc. (Fabaceae)] Produced in Côte d’Ivoire - N’Dri Yao, Denis (Int J Mol Sci, 2015)
The nutritional evaluation of the Bambara groundnut Ci12 landrace (Vigna subterranea (L.) Verdc.) seeds produced in Côte d’Ivoire shows a 19% content of protein, containing all the essential amino acids with tryptophan as the limiting amino acid, a total dietary fiber level of 10%, with a low soluble fraction content, and a fat content of 1.4%, with a high proportion of total unsaturated fatty acids (61%) of which 36% were n-6 fatty acids. This legume contains phosphorus, as the major mineral, followed by magnesium and calcium, and trace elements (iron, copper and zinc). It is characterized by the same amount of α-tocopherol and antioxidant capacity as common legumes. The high concentration of essential amino acids, n-6 fatty acids and minerals, mainly Fe, in the Ci12 landrace of Bambara groundnut indicates that this local legume has the potentiality to improve the nutritional status in Côte d’Ivoire and it could be regarded as a nutrient dense food.